1972
DOI: 10.1161/01.res.31.2.158
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Automaticity in Canine Purkinje Fibers Focally Subjected to Low External Concentrations of Calcium

Abstract: The false tendon was isolated from the dog heart and mounted under a partition plate in the center of a chamber which was filled with Tyrode's solution. Two microelectrodes were positioned closely on either side of the plate and inserted into the false tendon. The partition did not alter repolarization of the action potential in normal Tyrode's solution. When EDTA was added to one side of the preparation, a low-plateau potential appeared after repolarization on the other side, which contained normal Tyrone's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As demonstrated here, the longer the period of pacing, the greater the hyperpolarization of the fiber and the longer the duration of overdrive suppression. showed EAD-induced triggered activity at a potassium concentration of 2 mM and at cesium concentrations of 5 to 10 mM, 17 (89%) showed rapid inhibition of triggering when the external potassium concentration was raised to 4 mM ( figure 1 1). EAD magnitude was 7.5 ± 0.4 units with 2 mM potassium and 1.8 + 0.7 units 10 min after raising the potassium concentration to 4 mM (n = 19, p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated here, the longer the period of pacing, the greater the hyperpolarization of the fiber and the longer the duration of overdrive suppression. showed EAD-induced triggered activity at a potassium concentration of 2 mM and at cesium concentrations of 5 to 10 mM, 17 (89%) showed rapid inhibition of triggering when the external potassium concentration was raised to 4 mM ( figure 1 1). EAD magnitude was 7.5 ± 0.4 units with 2 mM potassium and 1.8 + 0.7 units 10 min after raising the potassium concentration to 4 mM (n = 19, p < .001).…”
Section: Resultsmentioning
confidence: 99%
“…Focal reexcitation has been demonstrated to occur by increasing inhomogeneity of repolarization in small segments of tissues. 17 A recent study also showed with experiments in vivo that ventricular arrhythmias were inducible in canine hearts in which dispersion of repolarization was induced by a combination of general hypothermia and selective coronary perfusion with warm blood. "8 The results of the present study, in agreement with those of previous reports,5-9 showed that ischemia produced by cessation of coronary perfusion shortened APD in affected myocardium, which may provide dispersion of repolarization between normal and ischemic myocardium in vivo.…”
mentioning
confidence: 96%
“…3 -* EADs have been induced in isolated cardiac tissue under a variety of conditions that increase inward current or reduce repolarizing current. These conditions include exposure to catecholamines, 7 acidosis, 8 low K + concentration, 9 low Ca 2+ concentration, 10 hypoxia, 11 and many drugs (e.g., aconitine, 12 quinidine, 5 7V-acetyl procainamide, 13 sotalol, 14 cesium chloride, 34 and clofilium 11 )-In vivo evidence of EAD and triggered activity as the underlying mechanism of polymorphic ventricular tachyarrhythmias in dogs exposed to cesium chloride was reported through the use of endocardial and epicardial monophasic action potentials. •Statistically significant (Student's t test, p<0.001); tstatistically significant (Student's t test, p<0.01).…”
mentioning
confidence: 99%